2012
DOI: 10.1111/j.1399-0039.2012.01931.x
|View full text |Cite
|
Sign up to set email alerts
|

Major histocompatibility complex class I chain related gene‐A microsatellite polymorphism shows secondary association with type 1 diabetes and celiac disease in North Indians

Abstract: Microsatellite polymorphism in exon 5 of major histocompatibility complex class I chain related gene-A (MIC-A) has been implicated in the etiology of autoimmune diseases including type 1 diabetes (T1D) and celiac disease (CD). In this study on North Indian population, the MIC-A5.1 allele, carrying a premature termination codon in transmembrane region, was observed with increased frequency in T1D (29.6%, odds ratio OR = 2.1, P = 0.00017) and CD patients (40.3%, OR = 3.37, P = 1.67E-05) than in controls (16.7%).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…The difference in the prevalence of CD across geographical locations was found to be due to difference in distribution of the HLA genotypes and its complex interaction with the environment and host immunological factors19. The association of T1DM and CD in north Indian population may be attributed to microsatellite polymorphism in major histocompatibility complex class I chain20. A multicentre study from Italy has demonstrated a positive association between young age at diabetes onset, female gender and the development of CD21.…”
Section: Discussionmentioning
confidence: 99%
“…The difference in the prevalence of CD across geographical locations was found to be due to difference in distribution of the HLA genotypes and its complex interaction with the environment and host immunological factors19. The association of T1DM and CD in north Indian population may be attributed to microsatellite polymorphism in major histocompatibility complex class I chain20. A multicentre study from Italy has demonstrated a positive association between young age at diabetes onset, female gender and the development of CD21.…”
Section: Discussionmentioning
confidence: 99%
“…The exon encodes membrane-binding domain of the protein [90]. The microsatellite alleles are associated with Addison's disease [90], type 1 diabetes mellitus [91,92,93]. Some alleles are protective against juvenile idiopathic arthritis [94].…”
Section: Dna Secondary Structurementioning
confidence: 99%
“…It was found that DR3 positive MICA5.1 positive and DR3+MICA5.1 negative individuals have similar relative risk suggesting that MICA5.1 has no independent association with T1DM. [ 3 ]…”
Section: O Ther G Enesmentioning
confidence: 99%